Functional structure

JP7644926B2Active Publication Date: 2025-03-13HOKKAIDO UNIVERSITY +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020559939
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-03
Filing Date
2019-12-03
Publication Date
2025-03-13
Estimated Expiration
2039-12-03

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、高い耐熱性を有し、高温で長期間使用しても機能性物質の機能低下を抑制して長寿命化を実現することができる機能性構造体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644926000005
    Figure 0007644926000005
  • Figure 0007644926000006
    Figure 0007644926000006
  • Figure 0007644926000007
    Figure 0007644926000007
Patent Text Reader

Abstract

The present invention provides a functional structure that has high heat resistance and can suppress functional degradation of functional substances even when used at high temperatures for long periods, thereby achieving a long life. The functional structure comprises a porous support made of a zeolite-type compound and at least one functional substance present in the support, the support having passages that communicate with each other, the functional substance present in at least the passages of the support, and the average inner diameter of the passages being 0.54 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a functional structure comprising a support (skeleton) with a porous structure and a functional substance. [Background technology]

[0002] Catalysts are used in a wide variety of applications, including the automotive and resource fields. For example, in the automotive field, a ceramic catalyst body has been proposed as a catalyst structure for exhaust gas from vehicles equipped with diesel engines, in which a ceramic carrier is disposed on the surface of a substrate ceramic and both a main catalyst component and a co-catalyst component are supported on the ceramic carrier. In this ceramic catalyst body, a large number of pores consisting of lattice defects in the crystal lattice are formed on the surface of the ceramic carrier made of γ-alumina, and the main catalyst component consisting of Ce-Zr, Pt, etc. is directly supported near the surface of the ceramic carrier (Patent Document 1).

[0003] Furthermore, a catalyst structure in which a metal catalyst is formed on a porous support (eg, porous silica) has been reported (Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] US Patent Application Publication No. 2016 / 0030934 [Patent Document 2] JP 2004-148166 A [Patent Document 3] JP 2000-72431 A [Patent Document 4] JP 2017-128480 A [Patent Document 5] International Publication No. 2010 / 097108 Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, automobile exhaust gas treatment catalysts (so-called three-way catalysts) are placed near the engine and can be heated by the heat generated by the engine. In addition, catalysts for the reverse shift reaction in C1 chemistry require high temperatures to proceed, so they are usually heated before use.

[0006] As described above, in a catalyst structure placed under high temperature conditions, catalyst particles move within the carrier due to high temperature heat, and the catalyst particles are likely to aggregate (sinter). When catalyst particles aggregate, the effective surface area of ​​the catalyst decreases, which reduces catalytic activity and shortens the catalyst life. In addition, the carrier also deteriorates at high temperatures. For example, the surface area of ​​ordinary porous silica can decrease significantly at high temperatures (Patent Document 3). This decrease in surface area increases the possibility of contact between catalyst particles, promoting aggregation.

[0007] When the agglomeration of catalyst particles progresses quickly, the catalyst structure itself must be replaced and regenerated in a short period of time, which makes the replacement work complicated and prevents resource saving. In addition, the suppression or prevention of such deterioration of function over time is cited as an issue not only in the field of catalysts but also in various technical fields, and a solution is desired to maintain the function for a long time. For example, in Patent Documents 4 and 5, a technology is reported in which amorphous silica-coated metal particles are produced by the emulsion method in order to suppress the agglomeration of catalysts, and then the particles are subjected to hydrothermal treatment to encapsulate the metal particles in zeolite. The production of amorphous silica-coated metal particles by the emulsion method is achieved by adding a reducing agent to an emulsion in which a surfactant and a metal source are mixed in an organic solvent to form metal particles, and then adding a silane coupling agent to form a silica layer on the surface of the metal particles. However, when producing metal particles by the emulsion method, the particle size of the obtained particles is affected by the size of the droplets when emulsified and the ease of agglomeration of the metal particles. In general, it is difficult to maintain the state of nanoparticles of base metals. In the examples of cited documents 4 and 5, nano-sized particles are described only in the case of precious metal samples, and nano-sized particles are not disclosed for samples of base metals and their oxides that tend to aggregate. Also, cited documents 4 and 5 report that in the emulsion method, organic solvents, surfactants, etc. remain, and reagents used in forming the zeolite structure become impurities, which adversely affect the thermal stability of zeolite.

[0008] An object of the present invention is to provide a functional structure which has high heat resistance and can suppress deterioration of the functions of functional substances even when used at high temperatures for a long period of time, thereby realizing a long life. [Means for solving the problem]

[0009] As a result of intensive research into achieving the above-mentioned object, the inventors have found that a functional structure can be obtained which comprises a framework which is a carrier having a porous structure composed of a zeolite-type compound, and at least one functional substance present in the framework, wherein the framework has passages which communicate with each other and the average inner diameter of the passages is 0.54 nm or less, and the functional substance is present at least in the passages of the framework, thereby suppressing deterioration in the function of the functional substance even when used for a long period of time at high temperatures and realizing a long life, and have completed the present invention based on this finding.

[0010] That is, the gist of the present invention is as follows. [1] A porous support composed of a zeolite-type compound; At least one functional substance present in the carrier; Equipped with The carrier has passages communicating with each other, the functional material is present in at least the passages of the carrier; A functional structure, characterized in that the average inner diameter of the passages is 0.54 nm or less. [2] The passage has one of one-dimensional pores, two-dimensional pores, and three-dimensional pores in the framework structure of the zeolite-type compound, and an expanded portion different from any of the one-dimensional pores, the two-dimensional pores, and the three-dimensional pores; and The functional structure according to [1], characterized in that the functional substance is present at least in the expanded diameter portion. [3] The functional structure according to [2], wherein the enlarged diameter portion connects a plurality of holes constituting any one of the one-dimensional hole, the two-dimensional hole, and the three-dimensional hole. [4] The functional material is a catalytic material; The functional structure according to any one of [1] to [3], wherein the support supports the at least one catalytic substance. [5] The functional structure according to [4], wherein the catalytic substance is metal oxide fine particles. [6] The functional structure according to [5], characterized in that the average particle size of the metal oxide microparticles is larger than the average inner diameter of the passages and is equal to or smaller than the inner diameter of the expanded portion. [7] The functional structure according to [5] or [6], wherein the metal oxide fine particles have an average particle size of 0.1 nm to 50 nm. [8] The functional structure according to any one of [5] to [7], wherein a ratio of an average particle diameter of the metal oxide microparticles to an average inner diameter of the passages is 0.06 to 500. [9] The functional structure according to [4], wherein the catalytic substance is a metal fine particle.

[10] The functional structure according to [9], characterized in that the average particle diameter of the metal microparticles is larger than the average inner diameter of the passage and is equal to or smaller than the inner diameter of the expanded portion.

[11] The functional structure according to [9] or

[10] , wherein the metal particles have an average particle size of 0.08 nm to 30 nm.

[12] The functional structure according to any one of [9] to

[11] , wherein a ratio of an average particle diameter of the metal microparticles to an average inner diameter of the passages is 0.05 to 300.

[13] The functional structure according to any one of [2] to

[12] , wherein the inner diameter of the expanded portion is 0.50 nm to 50 nm.

[14] The functional structure according to any one of [1] to

[13] , further comprising at least one other functional substance held on the outer surface of the carrier.

[15] The functional structure described in

[14] , characterized in that the content of the at least one functional substance contained within the carrier is greater than the content of the at least one other functional substance retained on the outer surface of the carrier.

[16] The functional structure according to any one of [1] to

[15] , wherein the zeolite type compound is a silicate compound.

[17] The functional structure described in any one of [1] to

[16] , characterized in that the zeolite-type compound has one or more skeletal structures selected from the group consisting of LTA, AFX, LEV, FER and CHA. Effect of the Invention

[0011] According to the present invention, it is possible to provide a functional structure that has high heat resistance and can suppress deterioration of the function of a functional substance even when used at high temperatures for a long period of time, thereby realizing a long life. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram showing the internal structure of a functional structure according to an embodiment of the present invention, with FIG. 1(a) being an oblique view (partially shown in cross section) and FIG. 1(b) being a partially enlarged cross-sectional view. [Diagram 2] 2A and 2B are partially enlarged cross-sectional views for explaining an example of the function of the functional structure of FIG. 1, where FIG. 2A illustrates the sieving function and FIG. 2B illustrates the catalytic function. [Diagram 3] FIG. 3 is a flowchart showing an example of a method for manufacturing the functional structure of FIG. [Figure 4] FIG. 4 is a schematic diagram showing a modified example of the functional structure of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.

[0014] [Configuration of functional structures] Fig. 1 is a diagram showing a schematic configuration of a functional structure according to an embodiment of the present invention, where (a) is a perspective view (partially shown in cross section), and (b) is a partially enlarged cross-sectional view. Note that the functional structure in Fig. 1 shows one example, and the shape, dimensions, etc. of each component according to the present invention are not limited to those in Fig. 1.

[0015] As shown in FIG. 1( a ), the functional structure 1 comprises a framework 10 which is a support having a porous structure composed of a zeolite-type compound, and at least one functional substance 20 present within the framework 10 .

[0016] The functional material 20 is a material that exerts one or more functions, either alone or in cooperation with the framework 10. Specific examples of the functions include a catalytic function, a light emitting (or fluorescent) function, a light absorbing function, and a recognition function. The functional material 20 is preferably a catalytic material having a catalytic function. When the functional material 20 is a catalytic material, the framework 10 is a carrier that supports the catalytic material.

[0017] In the functional structure 1, a plurality of functional substances 20, 20, ... are encapsulated within the porous structure of the framework 10. A catalytic substance, which is an example of the functional substance 20, is preferably at least one of metal oxide fine particles and metal fine particles. The metal oxide fine particles and metal fine particles will be described in detail later. The functional substance 20 may also be particles containing a metal oxide or metal alloy, or a composite material thereof.

[0018] The skeleton 10 has a porous structure, and preferably has a plurality of pores 11a, 11a, ... formed therein to form passages 11 communicating with each other, as shown in Fig. 1(b). The average inner diameter of the passages 11 is 0.54 nm or less. The functional substance 20 is present at least in the passages 11 of the skeleton 10, and is preferably retained in at least the passages 11 of the skeleton 10.

[0019] With this configuration, the movement of the functional material 20 within the framework 10 is restricted, and the aggregation of the functional materials 20, 20 with each other is effectively prevented. As a result, the reduction in the effective surface area of ​​the functional material 20 can be effectively suppressed, and the function of the functional material 20 is maintained for a long period of time. In other words, according to the functional structure 1, the deterioration of the function due to aggregation of the functional material 20 can be suppressed, and the life of the functional structure 1 can be extended. Furthermore, the extended life of the functional structure 1 can reduce the frequency of replacement of the functional structure 1, and the amount of waste of used functional structures 1 can be significantly reduced, thereby saving resources.

[0020] Usually, when a functional structure is used in a fluid (e.g., heavy oil or reformed gas such as NOx), it may be subjected to an external force from the fluid. In this case, if the functional substance is merely held in an attached state on the outer surface of the skeleton 10, there is a problem that the functional substance is easily detached from the outer surface of the skeleton 10 due to the influence of the external force from the fluid. In contrast, in the functional structure 1, the functional substance 20 is held at least in the passage 11 of the skeleton 10, so that the functional substance 20 is unlikely to be detached from the skeleton 10 even if it is affected by the external force of the fluid. That is, when the functional structure 1 is in a fluid, the fluid flows into the passage 11 from the hole 11a of the skeleton 10, so that the speed of the fluid flowing in the passage 11 is considered to be slower than the speed of the fluid flowing on the outer surface of the skeleton 10 due to the flow path resistance (friction force). Due to the influence of such flow path resistance, the pressure that the functional substance 20 held in the passage 11 receives from the fluid is lower than the pressure that the functional substance receives from the fluid outside the skeleton 10. Therefore, it is possible to effectively prevent the functional substance 20 contained in the skeleton 11 from being released, and to stably maintain the function of the functional substance 20 for a long period of time. Note that it is considered that the above-mentioned flow path resistance becomes larger as the passage 11 of the skeleton 10 has a plurality of bends and branches and the interior of the skeleton 10 has a more complex, three-dimensional structure.

[0021] In particular, when the average inner diameter of the passages 11 in the framework 10 is 0.54 nm or less, the heat resistance of the carrier itself is significantly improved and the aggregation of catalyst particles can be suppressed when the carrier is used in high-temperature environments (800°C or higher) such as automobile exhaust gas treatment and reverse shift reaction.

[0022] The average inner diameter D of the passage 11 formed in the skeleton 10 F is calculated from the average value of the minor axis and the major axis of the pores 11a constituting one of the one-dimensional pores, two-dimensional pores, and three-dimensional pores described later. F is preferably 0.54 nm or less, more preferably 0.50 nm or less, and further preferably 0.47 nm or less, 0.45 nm or less. When the average inner diameter of the passages 11 is within the above range, the heat resistance of the framework 10 is improved. In addition, the average inner diameter D Fis preferably 0.30 nm or more, and more preferably 0.32 nm or more. When the average inner diameter of the passages 11 is within the above range, it becomes possible to efficiently introduce raw materials for catalytic reaction into the inside of the framework 10.

[0023] Moreover, the passage 11 preferably has one of one-dimensional, two-dimensional and three-dimensional pores defined by the framework structure of the zeolite-type compound, and an expanded diameter portion 12 different from any of the one-dimensional, two-dimensional and three-dimensional pores. In this case, the functional substance 20 is preferably present at least in the expanded diameter portion 12, and more preferably is included in at least the expanded diameter portion 12. The one-dimensional pore here refers to a tunnel-type or cage-type pore forming a one-dimensional channel, or a plurality of tunnel-type or cage-type pores (a plurality of one-dimensional channels) forming a plurality of one-dimensional channels. The two-dimensional pore refers to a two-dimensional channel in which a plurality of one-dimensional channels are two-dimensionally connected, and the three-dimensional pore refers to a three-dimensional channel in which a plurality of one-dimensional channels are three-dimensionally connected. This further restricts the movement of the functional substance 20 within the framework 10, and makes it possible to more effectively prevent the functional substance 20 from being separated or the functional substances 20, 20 from aggregating together. Inclusion refers to a state in which the functional substance 20 is encapsulated in the framework 10. In this case, the functional substance 20 and the framework 10 do not necessarily need to be in direct contact with each other, and the functional substance 20 may be indirectly held in the framework 10 with another substance (e.g., a surfactant, etc.) intervening between the functional substance 20 and the framework 10.

[0024] 1(b) shows a case where the functional substance 20 is encapsulated in the enlarged diameter portion 12, but the present invention is not limited to this configuration, and the functional substance 20 may be held in the passage 11 with a part of it protruding outside the enlarged diameter portion 12. The functional substance 20 may also be partially embedded in a part of the passage 11 other than the enlarged diameter portion 12 (for example, an inner wall part of the passage 11) or held by adhesion or the like. In addition, it is preferable that the expanded diameter portion 12 communicates with the plurality of holes 11a, 11a constituting any one of the one-dimensional holes, the two-dimensional holes, and the three-dimensional holes, so that a separate passage different from the one-dimensional holes, the two-dimensional holes, or the three-dimensional holes is provided inside the framework 10, thereby enabling the function of the functional substance 20 to be more effectively exhibited.

[0025] Moreover, the passage 11 is formed three-dimensionally inside the framework 10 including a branching portion or a junction portion, and the enlarged diameter portion 12 is preferably provided at the branching portion or the junction portion of the passage 11 .

[0026] Inner diameter D of the expanded diameter portion 12 E The inner diameter D of the expanded diameter portion 12 is, for example, 0.5 nm to 50 nm, preferably 1.1 nm to 40 nm, and more preferably 1.1 nm to 3.3 nm. E is, for example, the pore size of the precursor material (A) described later and the average particle size D of the functional material 20 to be enclosed. C The inner diameter D of the expanded diameter portion 12 depends on E is a size capable of encapsulating the functional substance 20.

[0027] The framework 10 is composed of a zeolite-type compound. Examples of the zeolite-type compound include silicate compounds such as zeolite (aluminosilicate), cation-exchanged zeolite, and silicalite, zeolite-related compounds such as aluminoborates, aluminoarsenates, and germanates, and phosphate-based zeolite-like substances such as molybdenum phosphate. Among these, the zeolite-type compound is preferably a silicate compound.

[0028] The framework structures of zeolite-type compounds are represented by the following structure codes: ABW, ACO, AEI, AEN, AFO, AFT, AFV, AFX, APC, APD, ASV, ATN, ATO, ATT, ATV, AVL, AWO, AWW, BIK, BOF, BRE, BSV, CAS, CDO, CGF, CGS, CHA, CHI, DAC, DDR, DFT, EAB, EDI, EEI, EPI, ERI, ESV, ETL, EU. It is selected from among O, FER, GIS, GOO, IFY, IHW, IRN, ITE, ITH, ITW, JBW, JOZ, JSN, JSW, KFI, LAU, LEV, LOV, LTA, LTJ, MEL, MER, MFS, MON, MTF, MTT, MVY, MWF, NAB, NAT, NPO, NPT, NSI, OBW, OWE, PAU, PHI, PON, RHO, RON, RSN, RTE, etc. Preferred are LTA, AFX, LEV, FER, and CHA.

[0029] Hereinafter, a detailed description will be given of the case where the functional material 20 is at least one of metal oxide fine particles and metal fine particles (hereinafter, these may be collectively referred to as "fine particles").

[0030] When the functional material 20 is the above-mentioned fine particles, the fine particles 20 may be primary particles or secondary particles formed by aggregation of the primary particles. C That is, the average particle diameter of the metal oxide fine particles or the average particle diameter of the metal fine particles is preferably equal to or smaller than the average inner diameter D F and the inner diameter D of the expanded diameter portion 12 is larger than E The following is true: F <D C ≦D E ). In the passage 11, such microparticles 20 are preferably enclosed in the enlarged diameter portions 12, and the movement of the microparticles 20 in the skeleton 10 is restricted. Therefore, even if the microparticles 20 are subjected to an external force from the fluid, the movement of the microparticles 20 in the skeleton 10 is restricted, and the microparticles 20, 20, ... enclosed in the enlarged diameter portions 12, 12, ... dispersed and arranged in the passage 11 of the skeleton 10 can be effectively prevented from contacting each other.

[0031] When the functional material 20 is metal oxide fine particles, the average particle diameter D of the metal oxide fine particles 20 C In both the case of the primary particles and the secondary particles, the average inner diameter D of the passages 11 is preferably 0.1 nm to 50 nm, more preferably 0.1 nm or more and less than 30 nm, further preferably 0.4 nm to 14.0 nm, and particularly preferably 1.0 nm to 3.3 nm. F Average particle size D of metal oxide fine particles 20 C Percentage of (D C / D F ) is preferably 0.06 to 500, more preferably 0.1 to 36, further preferably 1.1 to 36, and particularly preferably 1.7 to 4.5.

[0032] Furthermore, when the functional substance 20 is metal oxide microparticles, the metal element (M) of the metal oxide microparticles is preferably contained in an amount of 0.5 to 2.5 mass % relative to the functional structure 1, and more preferably 0.5 to 1.5 mass % relative to the functional structure 1. For example, when the metal element (M) is Co, the content (mass %) of the Co element is expressed as (mass of Co element) / (mass of all elements in the functional structure 1)×100.

[0033] The metal oxide microparticles may be composed of a metal oxide, and may be composed of, for example, a single metal oxide or a mixture of two or more metal oxides. In this specification, the term "metal oxide" (as a material) constituting the metal oxide microparticles means a metal oxide containing one metal element (M) and a metal composite oxide containing two or more metal elements (M), and is a general term for oxides containing one or more metal elements (M).

[0034] Examples of such metal oxides include cobalt oxide (CoO x ), Nickel oxide (NiO x ), iron oxide (FeO x ), copper oxide (CuO x ), zirconium oxide (ZrO x ), cerium oxide (CeO x), aluminum oxide (AlO x ), niobium oxide (NbO x ), titanium dioxide (TiO x ), bismuth oxide (BiO x ), molybdenum oxide (MoO x ), vanadium oxide (VO x ), chromium oxide (CrO x ) and the like, and it is preferable to use one or more of the above as the main component.

[0035] In addition, when the functional material 20 is metal fine particles, the average particle diameter D C In both the case of the primary particles and the secondary particles, the average inner diameter D of the passages 11 is preferably 0.08 to 30 nm, more preferably 0.08 nm or more and less than 25 nm, further preferably 0.4 nm to 11.0 nm, and particularly preferably 0.8 to 2.7 nm. F Average particle size D of metal particles 20 C Percentage of (D C / D F ) is preferably 0.05 to 300, more preferably 0.1 to 30, further preferably 1.1 to 30, and particularly preferably 1.4 to 3.6.

[0036] When the functional material 20 is a metal microparticle, the metal element (M) of the metal microparticle is preferably contained in an amount of 0.5 to 7.6 mass% relative to the functional structure 1, more preferably 0.5 to 6.9 mass%, even more preferably 0.5 to 2.5 mass%, and most preferably 0.5 to 1.5 mass%.

[0037] The metal microparticles may be made of a non-oxidized metal, and may be made of, for example, a single metal or a mixture of two or more metals. In this specification, the term "metal" (as a material) constituting the metal microparticles means a simple metal containing one metal element (M) and an alloy or mixture formed of two or more metal elements (M), and is a general term for metals containing one or more metal elements.

[0038] Examples of such metals include platinum (Pt), palladium (Pd), ruthenium (Ru), nickel (Ni), cobalt (Co), molybdenum (Mo), tungsten (W), iron (Fe), chromium (Cr), cerium (Ce), copper (Cu), magnesium (Mg), and aluminum (Al). It is preferable to use one or more of the above as the main component.

[0039] From the viewpoint of durability, the functional material 20 is preferably metal oxide fine particles.

[0040] Moreover, the ratio of silicon (Si) constituting the framework 10 to the metal element (M) constituting the microparticles 20 (atomic ratio Si / M) is preferably 10 to 1000, more preferably 50 to 200. If the ratio is more than 1000, the activity may be low and the effect as a functional material may not be sufficiently obtained. On the other hand, if the ratio is less than 10, the ratio of the microparticles 20 becomes too large, and the strength of the framework 10 tends to decrease. Note that the microparticles 20 referred to here refer to microparticles held or supported inside the framework 10, and do not include microparticles attached to the outer surface of the framework 10.

[0041] [Functions of functional structures] As described above, the functional structure 1 includes a skeleton 10 having a porous structure and at least one functional substance 20 present in the skeleton. The functional structure 1 exerts a function according to the functional substance 20 by contacting the functional substance 20 present in the skeleton with a fluid. Specifically, the fluid that contacts the outer surface 10a of the functional structure 1 flows into the skeleton 10 through the holes 11a formed in the outer surface 10a, is guided into the passage 11, moves through the passage 11, and exits the functional structure 1 through another hole 11a. In the path along which the fluid moves through the passage 11, the fluid comes into contact with the functional substance 20 held in the passage 11, causing a reaction (e.g., a catalytic reaction) according to the function of the functional substance 20. In addition, the functional structure 1 has a molecular sieving function due to the porous structure of the skeleton.

[0042] First, the molecular sieving ability of the functional structure 1 will be described with reference to FIG. 2(a) using an example in which the fluid is a liquid containing benzene, propylene, and mesitylene. As shown in FIG. 2(a), compounds (e.g., benzene, propylene) composed of molecules having a size equal to or smaller than the pore size of the hole 11a, in other words, equal to or smaller than the inner diameter of the passage 11, can penetrate into the framework 10. On the other hand, compounds (e.g., mesitylene) composed of molecules having a size larger than the pore size of the hole 11a cannot penetrate into the framework 10. In this way, when the fluid contains multiple types of compounds, the reaction of the compounds that cannot penetrate into the framework 10 is restricted, and the compounds that can penetrate into the framework 10 can be reacted.

[0043] Of the compounds produced in the framework 10 by the reaction, only compounds composed of molecules having a size equal to or smaller than the diameter of the holes 11a can escape to the outside of the framework 10 through the holes 11a and are obtained as reaction products. On the other hand, compounds that cannot escape to the outside of the framework 10 through the holes 11a can be escaped to the outside of the framework 10 if they are converted into compounds composed of molecules of a size that can escape to the outside of the framework 10. In this way, by using the functional structure 1, a specific reaction product can be selectively obtained.

[0044] In the functional structure 1, as shown in FIG. 2(b), the functional material 20 is preferably included in the expanded diameter portion 12 of the passage 11. The average particle diameter D of the functional material 20 is C is the average inner diameter D of passage 11 F The inner diameter D of the expanded diameter portion 12 is larger than E If it is smaller than (D F <D C <D E), a small passage 13 is formed between the functional substance 20 and the enlarged diameter portion 12. Then, as shown by the arrow in FIG. 2(b), the fluid that has entered the small passage 13 comes into contact with the functional substance 20. Since each functional substance 20 is encapsulated in the enlarged diameter portion 12, movement within the framework 10 is restricted. This prevents aggregation of the functional substances 20 within the framework 10. As a result, a large contact area between the functional substances 20 and the fluid can be stably maintained.

[0045] In particular, when the average inner diameter of the passages 11 in the framework 10 is 0.54 nm or less, the heat resistance of the carrier itself is significantly improved and the aggregation of catalyst particles can be suppressed when the carrier is used in high-temperature environments (800°C or higher) such as automobile exhaust gas treatment and reverse shift reaction.

[0046] Next, a case where the functional material 20 has a catalytic function will be described. Specifically, when the functional material 20 is nickel oxide (NiOx) fine particles, the functional material 20 can be used as a catalyst for, for example, a dry reforming reaction. This dry reforming reaction is represented by the following reaction formula, and CO 2 and C.H. 4 is used as a raw material to produce synthetic gas (CO and H) that is used as a raw material for various petrochemical products (lower alcohols, hydrocarbons, etc.). 2 ) is manufactured. CO 2 +CH 4 →2CO+2H 2

[0047] [Method of manufacturing functional structures] Fig. 3 is a flowchart showing a method for producing the functional structure 1 of Fig. 1. Hereinafter, an example of the method for producing the functional structure will be described taking as an example a case where the functional substance present in the framework is metal oxide fine particles.

[0048] (Step S1: Preparation process) First, a precursor material (A) for obtaining a porous structure framework composed of a zeolite-type compound is prepared as shown in Fig. 3. The precursor material (A) is preferably a regular mesoporous substance, and can be appropriately selected depending on the type (composition) of the zeolite-type compound that constitutes the framework of the functional structure.

[0049] Here, when the zeolite-type compound constituting the framework of the functional structure is a silicate compound, the regular mesoporous material is preferably a compound consisting of a Si-O framework in which pores with a pore diameter of 1 to 50 nm are uniform in size and regularly developed in one, two or three dimensions. Such regular mesoporous materials can be obtained as various synthetic products depending on the synthesis conditions, and specific examples of synthetic products include SBA-1, SBA-15, SBA-16, KIT-6, FSM-16, MCM-41, etc., and among them, MCM-41 is preferable. The pore diameter of SBA-1 is 10 to 30 nm, the pore diameter of SBA-15 is 6 to 10 nm, the pore diameter of SBA-16 is 6 nm, the pore diameter of KIT-6 is 9 nm, the pore diameter of FSM-16 is 3 to 5 nm, and the pore diameter of MCM-41 is 1 to 10 nm. Examples of such regular mesoporous substances include mesoporous silica, mesoporous aluminosilicate, and mesoporous metallosilicate.

[0050] The precursor material (A) may be either a commercially available product or a synthetic product. The precursor material (A) can be synthesized by a known method for synthesizing regular mesoporous materials. For example, a mixed solution containing raw materials containing the constituent elements of the precursor material (A) and a template agent for defining the structure of the precursor material (A) is prepared, and the pH is adjusted as necessary to perform hydrothermal treatment (hydrothermal synthesis). Thereafter, the precipitate (product) obtained by the hydrothermal treatment is collected (for example, filtered), washed and dried as necessary, and further calcined to obtain the precursor material (A), which is a powdered regular mesoporous material. Here, the solvent for the mixed solution can be, for example, water, an organic solvent such as alcohol, or a mixed solvent thereof. The raw material is selected according to the type of framework, and examples thereof include silica agents such as tetraethoxysilane (TEOS), fumed silica, and quartz sand. As the template agent, various surfactants, block copolymers, etc. can be used, and it is preferable to select according to the type of the ordered mesoporous material. For example, when preparing MCM-41, a surfactant such as hexadecyltrimethylammonium bromide is suitable. The hydrothermal treatment can be carried out, for example, in a closed vessel under the treatment conditions of 80 to 800°C, 5 to 240 hours, and 0 to 2000 kPa. The calcination treatment can be carried out, for example, in air under the treatment conditions of 350 to 850°C, 2 to 30 hours.

[0051] (Step S2: Impregnation process) Next, the prepared precursor material (A) is impregnated with a metal-containing solution to obtain a precursor material (B).

[0052] The metal-containing solution may be any solution containing a metal component (e.g., metal ion) corresponding to the metal element (M) constituting the metal oxide microparticles of the functional structure, and may be prepared, for example, by dissolving a metal salt containing the metal element (M) in a solvent. Examples of such metal salts include metal salts such as chlorides, hydroxides, oxides, sulfates, and nitrates, and among these, nitrates are preferred. Examples of the solvent that can be used include water, organic solvents such as alcohol, and mixtures thereof.

[0053] The method of impregnating the precursor material (A) with the metal-containing solution is not particularly limited, but for example, it is preferable to add the metal-containing solution in small amounts in multiple batches while stirring the powdered precursor material (A) before the firing step described below. In addition, from the viewpoint of making it easier for the metal-containing solution to penetrate into the pores of the precursor material (A), it is preferable to add a surfactant as an additive to the precursor material (A) before adding the metal-containing solution. Such an additive has the function of coating the outer surface of the precursor material (A), and is thought to suppress the adhesion of the metal-containing solution added thereafter to the outer surface of the precursor material (A), making it easier for the metal-containing solution to penetrate into the pores of the precursor material (A).

[0054] Examples of such additives include nonionic surfactants such as polyoxyethylene oleyl ether, polyoxyethylene alkyl ether, and polyoxyethylene alkyl phenyl ether. These surfactants have a large molecular size and cannot penetrate into the pores of the precursor material (A), so they do not adhere to the pores and do not prevent the metal-containing solution from penetrating into the pores. As a method for adding the nonionic surfactant, for example, it is preferable to add 50 to 500 mass% of the nonionic surfactant to the precursor material (A) before the firing step described below. If the amount of the nonionic surfactant added to the precursor material (A) is less than 50 mass%, the above-mentioned suppression effect is difficult to be exhibited, and if the nonionic surfactant is added to the precursor material (A) in excess of 500 mass%, the viscosity increases too much, which is not preferable. Therefore, the amount of the nonionic surfactant added to the precursor material (A) is set to a value within the above range.

[0055] In addition, the amount of the metal-containing solution added to the precursor material (A) is preferably adjusted appropriately in consideration of the amount of the metal element (M) contained in the metal-containing solution impregnated into the precursor material (A) (i.e., the amount of the metal element (M) to be contained in the precursor material (B)). For example, before the firing step described below, the amount of the metal-containing solution added to the precursor material (A) is preferably adjusted to be 10 to 1000, more preferably 50 to 200, in terms of the ratio of silicon (Si) constituting the precursor material (A) to the metal element (M) contained in the metal-containing solution added to the precursor material (A) (atomic ratio Si / M). For example, in the case where a surfactant is added to the precursor material (A) as an additive before the addition of the metal-containing solution to the precursor material (A), the amount of the metal-containing solution added to the precursor material (A) is adjusted to be 50 to 200 in terms of the atomic ratio Si / M, so that the metal element (M) of the metal oxide fine particles can be contained in at least 0.5 to 7.6 mass% relative to the functional structure. The amount of metal element (M) present inside the pores of the precursor material (B) is roughly proportional to the amount of metal-containing solution added to the precursor material (A) under the same conditions such as the metal concentration of the metal-containing solution, the presence or absence of the additive, and other conditions such as temperature and pressure. The amount of metal element (M) present in the precursor material (B) is also proportional to the amount of metal element constituting the metal oxide microparticles present in the framework of the functional structure. Therefore, by controlling the amount of metal-containing solution added to the precursor material (A) within the above range, the metal-containing solution can be sufficiently impregnated into the pores of the precursor material (A), and the amount of metal oxide microparticles present in the framework of the functional structure can be adjusted.

[0056] After the precursor material (A) is impregnated with the metal-containing solution, a washing process may be performed as necessary. As the washing solution, water, an organic solvent such as alcohol, or a mixture of these can be used. In addition, after the precursor material (A) is impregnated with the metal-containing solution and washed as necessary, it is preferable to further perform a drying process. Examples of the drying process include natural drying for about one night, and high-temperature drying at 150°C or less. Note that if the calcination process described below is performed while a large amount of moisture contained in the metal-containing solution or the moisture of the washing solution remains in the precursor material (A), the skeleton structure of the precursor material (A) as a regular mesoporous material may be destroyed, so it is preferable to dry it thoroughly.

[0057] (Step S3: Firing process) Next, precursor material (A) for obtaining a porous framework composed of a zeolite-type compound is impregnated with a metal-containing solution to obtain precursor material (B), which is then calcined to obtain precursor material (C).

[0058] The calcination treatment is preferably carried out in air at 350 to 850° C. for 2 to 30 hours. By such a calcination treatment, the metal component impregnated in the pores of the ordered mesoporous material undergoes crystal growth, forming metal oxide fine particles in the pores.

[0059] (Step S4: Hydrothermal treatment process) Next, a mixed solution is prepared by mixing the precursor material (C) and a structure directing agent, and the precursor material (C) obtained by calcining the precursor material (B) is subjected to a hydrothermal treatment to obtain a functional structure.

[0060] The structure-directing agent is a template agent for determining the skeletal structure of the skeleton of the functional structure, and for example, a surfactant can be used. The structure-directing agent is preferably selected according to the skeleton structure of the skeleton of the functional structure, and for example, surfactants such as TPABr, pyridine, TMAOH, TMAdaOH, piperidine, ethylenediamine, and amine compounds represented by the following formulas (1) and (2) are suitable. Note that OH, which is the counter anion of the amine compounds represented by the following formulas (1) and (2), - Br- , Cl - One type of the above may be used, or two or more types may be used in appropriate combination. [ka] [ka]

[0061] The precursor material (C) and the structure-directing agent may be mixed during the hydrothermal treatment process or before the hydrothermal treatment process. The method for preparing the mixed solution is not particularly limited, and the precursor material (C), the structure-directing agent, and the solvent may be mixed at the same time, or the precursor material (C) and the structure-directing agent may be dispersed in the solvent in their respective solutions, and then the respective dispersion solutions may be mixed. As the solvent, for example, water, an organic solvent such as alcohol, or a mixture of these may be used. It is also preferable to adjust the pH of the mixed solution using an acid or a base before performing the hydrothermal treatment.

[0062] The hydrothermal treatment can be carried out by a known method, and is preferably carried out in a sealed container under treatment conditions of 80 to 800° C., 5 to 240 hours, and 0 to 2000 kPa. The hydrothermal treatment is also preferably carried out in a basic atmosphere. Although the reaction mechanism here is not entirely clear, by carrying out hydrothermal treatment using precursor material (C) as a raw material, the skeletal structure of precursor material (C) as a regular mesoporous substance gradually collapses, but the positions of the metal oxide particles inside the pores of precursor material (C) are roughly maintained, and a new skeletal structure (porous structure) is formed as the skeleton of the functional structure due to the action of the structure-directing agent. The functional structure thus obtained comprises a skeleton with a porous structure and metal oxide particles contained within the skeleton, and furthermore, the skeleton has passages in which a plurality of pores are interconnected due to the porous structure, and at least a portion of the metal oxide particles are held in the passages of the skeleton. In addition, in the present embodiment, in the above-mentioned hydrothermal treatment step, a mixed solution is prepared by mixing the precursor material (C) and the structure-directing agent, and the precursor material (C) is hydrothermally treated. However, this is not limited thereto, and the precursor material (C) may be hydrothermally treated without mixing the precursor material (C) with the structure-directing agent.

[0063] The precipitate (functional structure) obtained after the hydrothermal treatment is preferably washed, dried and calcined as necessary after recovery (for example, filtration). As the washing solution, water, an organic solvent such as alcohol, or a mixture of these can be used. As the drying treatment, natural drying for about one night or high-temperature drying at 150°C or less can be used. If the precipitate is calcined while a large amount of moisture remains, the skeleton structure as the skeleton of the functional structure may be destroyed, so it is preferable to dry it thoroughly. In addition, the calcination treatment can be performed, for example, in air at 350 to 850°C for 2 to 30 hours. By such a calcination treatment, the structure-directing agent attached to the functional structure is burned off. In addition, the functional structure can be used as it is without calcining the precipitate after recovery depending on the purpose of use. For example, when the environment in which the functional structure is used is a high-temperature environment in an oxidizing atmosphere, the structure-directing agent is burned off by exposing it to the use environment for a certain period of time, and the functional structure can be obtained similar to that obtained by calcination treatment, so that it can be used as it is.

[0064] Although the above has been described by taking the example of a method for producing a functional structure in which the functional substance is metal oxide fine particles, a functional structure can be produced in the same manner as above when the functional substance is metal fine particles. For example, after obtaining a functional structure having metal oxide particles as described above, a reduction treatment is performed under a reducing gas atmosphere such as hydrogen gas to obtain a functional structure in which metal fine particles are present in a framework. In this case, the metal oxide fine particles present in the framework are reduced to form metal fine particles corresponding to the metal element (M) constituting the metal oxide fine particles. Alternatively, by using a metal element (M) contained in a metal-containing solution to be impregnated into the precursor material (A) as a metal species that is difficult to oxidize (e.g., a noble metal), the metal fine particles can be crystal-grown in the firing step (step S3), and then a hydrothermal treatment is performed to obtain a functional structure in which metal fine particles are present in a framework.

[0065] [Modification of functional structure 1] FIG. 4 is a schematic diagram showing a modified example of the functional structure 1 of FIG. The functional structure 1 in Figure 1 is shown to have a skeleton 10 and a functional substance 20 contained within the skeleton 10, but is not limited to this configuration. For example, as shown in Figure 4, the functional structure 2 may further have another functional substance 30 held on the outer surface 10a of the skeleton 10.

[0066] This functional material 30 is a material that exerts one or more functions. The function possessed by the other functional material 30 may be the same as or different from the function possessed by the functional material 20. Specific examples of the functions possessed by the other functional material 30 are the same as those described for the functional material 20, and among them, it is preferable that the other functional material 30 has a catalytic function, in which case the functional material 30 is a catalytic material. In addition, when both the functional materials 20 and 30 are materials having the same function, the material of the other functional material 30 may be the same as or different from the material of the functional material 20. According to this configuration, the content of the functional material held in the functional structure 2 can be increased, and the function exertion of the functional material can be further promoted.

[0067] In this case, the content of the functional substance 20 present in the framework 10 is preferably greater than the content of the other functional substances 30 held on the outer surface 10a of the framework 10. This allows the function of the functional substance 20 held inside the framework 10 to predominate, and the function of the functional substance is stably exerted.

[0068] Although the functional structure according to the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications and changes are possible based on the technical concept of the present invention. EXAMPLES

[0069] (Examples 1 to 50) [Synthesis of precursor material (A)] A mixed aqueous solution was prepared by mixing a silica agent (tetraethoxysilane (TEOS), manufactured by Wako Pure Chemical Industries, Ltd.) and a surfactant as a structure-directing agent (template agent), and the pH was appropriately adjusted. The solution was subjected to hydrothermal treatment at 80 to 350°C for 100 hours in a sealed container. The precipitate formed was then filtered, washed with water and ethanol, and further calcined in air at 600°C for 24 hours to obtain precursor materials (A) of the types and pore sizes shown in Tables 1 and 2. The structure-directing agents (surfactants) used were as follows according to the type of precursor material (A) ("Type of precursor material (A): Surfactant"). In Tables 1 and 2, the amines of the above formulas (1) and (2) are referred to as "Amine 1" and "Amine 2", respectively. MCM-41: Hexadecyltrimethylammonium bromide (CTAB) (Wako Pure Chemical Industries, Ltd.) SBA-1: Pluronic P123 (BASF)

[0070] [Preparation of precursor materials (B) and (C)] Next, metal-containing aqueous solutions were prepared by dissolving metal salts containing the metal elements (M) constituting the metal oxide microparticles of the types shown in Tables 1 and 2 in water. The metal salts used were as follows, depending on the type of metal oxide microparticles ("metal oxide microparticles: metal salt"). CoO x : Cobalt(II) nitrate hexahydrate (manufactured by Wako Pure Chemical Industries, Ltd.) NiO x Nickel (II) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd.) FeO x :Iron(III) nitrate nonahydrate (manufactured by Wako Pure Chemical Industries, Ltd.)

[0071] Next, the metal-containing aqueous solution was added in small amounts in several batches to the powdered precursor material (A), and the mixture was dried at room temperature (20° C.±10° C.) for 12 hours or more to obtain a precursor material (B).

[0072] In all of the examples, the precursor material (A) was pretreated with an aqueous solution of polyoxyethylene (15) oleyl ether (NIKKOL BO-15V, manufactured by Nikko Chemicals Co., Ltd.) as an additive before the addition of the metal-containing aqueous solution, and then the metal-containing aqueous solution was added as described above.

[0073] In addition, the amount of the metal-containing aqueous solution added to the precursor material (A) was adjusted so that the ratio of silicon (Si) constituting the precursor material (A) to the metal element (M) contained in the metal-containing aqueous solution (atomic number ratio Si / M) would be 100.

[0074] Next, the precursor material (B) impregnated with the metal-containing aqueous solution obtained as above was calcined in air at 600° C. for 24 hours to obtain a precursor material (C).

[0075] [Synthesis of functional structures] The precursor material (C) obtained as described above was mixed with a structure directing agent shown in Tables 1 and 2 to prepare a mixed aqueous solution, which was then subjected to hydrothermal treatment in a closed container at 40 to 350°C, pH 7 to 12, and 5 to 240 hours. The resulting precipitate was then filtered, washed with water, dried at 100°C for 12 hours or more, and then fired in air at 600°C for 24 hours. The fired product was then collected to obtain a functional structure having a framework shown in Tables 1 and 2 and metal fine particles as a functional substance.

[0076] Comparative Example 1 In Comparative Example 1, a functional structure was obtained in the same manner as in Example 2, except that no structure-directing agent was used.

[0077] [evaluation] The functional structures of the above-mentioned Examples and Comparative Examples were subjected to various property evaluations under the conditions shown below.

[0078] [A] Cross-section observation For the functional structures of the above-mentioned Examples and Comparative Examples, observation samples were prepared by a pulverization method, and cross-sections were observed using a transmission electron microscope (TEM) (TITAN G2, manufactured by FEI).

[0079] As a result, it was confirmed that in the functional structures of the above-mentioned Examples and Comparative Examples, the functional substance was present and held inside the framework made of zeolite.

[0080] In addition, for the functional structures in the above examples in which the metal oxide was iron oxide fine particles (FeOx), cross sections were cut out by FIB (focused ion beam) processing, and cross-sectional elemental analysis was performed using a SEM (SU8020, Hitachi High-Technologies Corporation) and an EDX (X-Max, Horiba, Ltd.) As a result, Fe elements were detected from inside the framework.

[0081] The above-mentioned cross-sectional observations by TEM and SEM / EDX confirmed the presence of iron oxide particles inside the framework.

[0082] [B] Average inner diameter of the pathways in the framework and average particle size of the functional material In the TEM image taken by the cross-sectional observation performed in the above evaluation [A], 500 passages of the skeleton were randomly selected, the long and short diameters of each were measured, and the inner diameter of each was calculated from the average value (N=500). The average inner diameter was then calculated to obtain the average inner diameter D FSimilarly, for the functional substance, 500 functional substances were randomly selected from the above TEM image, and the particle size of each was measured (N=500), and the average value was calculated to obtain the average particle size D C The results are shown in Table 1.

[0083] In addition, to confirm the average particle size and dispersion state of the functional material, analysis was performed using SAXS (small angle X-ray scattering). Measurements using SAXS were performed using beamline BL19B2 at Spring-8. The obtained SAXS data was fitted with a spherical model using the Guinier approximation method to calculate the particle size. The particle size was measured for the functional structures of Examples 3, 5, 13, 15, 23, 25, 33, 35, 43, and 45, in which the metal oxide was iron oxide fine particles. In addition, for comparison, commercially available iron oxide fine particles (manufactured by Wako) were observed and measured by SEM.

[0084] As a result, it was found that while commercially available products contain randomly distributed iron oxide microparticles of various sizes in the particle size range of approximately 50 nm to 400 nm, the functional structures of Examples 3, 5, 13, 15, 23, 25, 33, 35, 43 and 45 all contained iron oxide microparticles with particle sizes of 1 to 20 nm that were uniform in size and in a highly dispersed state within the framework.

[0085] [C] Performance evaluation The performance of the functional substance (catalyst substance) was evaluated for the functional structures of the above-mentioned Examples and Comparative Examples. The results are shown in Table 1.

[0086] (1) Heat resistance (life span) The functional structures shown in the examples and comparative examples were heated in an air atmosphere at 800°C for 12 hours, and the functional structures before and after the heating were measured using a D8 Advance (Bruker) to obtain XRD patterns. In the obtained XRD pattern of the functional structure before heating, the peak having the highest intensity at 2θ=15° or less (hereinafter referred to as the "main peak") was adopted as a representative value, and the heat resistance index was calculated using the following formula using this value. Heat resistance index = (XRD main peak intensity value after heating / XRD main peak intensity value before heating) x 100

[0087] The heat resistance index indicates the degree of suppression of the decrease in crystallinity of the skeleton before and after heating, and a larger index indicates higher crystallinity. Specifically, the heat resistance was judged based on the following criteria. If it is 90% or more, it is judged to have good heat resistance and is given a "◎" rating. If it is between 70% and 90%, the heat resistance is deemed fair and is marked as "○". If it is less than 70%, it is judged to be insufficient in heat resistance and marked as "X".

[0088] (2) Catalytic activity From Examples 1 to 30, it was found that heat resistance was expressed by setting the pore diameter of the zeolite to 0.54 nm or less. Next, the functional structure was heated in an air atmosphere at 650° C. for 12 hours, and the activity before and after the heating was confirmed. Here, Examples 1 to 3, which were evaluated as having heat resistance of ○, and Examples 4 to 5, which were evaluated as having heat resistance of ⊚, were selected as samples.

[0089] The catalytic activity was evaluated under the following conditions. First, 0.2 g of the functional structure was packed into a normal pressure flow type reaction apparatus, and nitrogen gas (N 2 The decomposition reaction of butylbenzene (a model substance of heavy oil) was carried out at 400°C for 2 hours using benzene as a carrier gas (5 ml / min).

[0090] After the reaction was completed, the recovered product gas and product liquid were analyzed for their components by gas chromatography (GC) and gas chromatography mass spectrometry (GC / MS). The analytical instruments used were a TRACE 1310GC (manufactured by Thermo Fisher Scientific, Inc., detectors: thermal conductivity detector, hydrogen flame ionization detector) and a TRACE DSQ (manufactured by Thermo Fisher Scientific, Inc., detector: mass detector, ionization method: EI (ion source temperature 250°C, MS transfer line temperature 320°C).

[0091] Furthermore, based on the results of the above component analysis, the yield (mol%) of compounds having a molecular weight smaller than that of butylbenzene (specifically, benzene, toluene, ethylbenzene, styrene, cumene, methane, ethane, ethylene, propane, propylene, butane, butene, etc.) was determined. The yield of the above compounds was calculated as the percentage (mol%) of the total amount (mol) of the substances of compounds having a molecular weight smaller than that of butylbenzene contained in the product liquid relative to the amount (mol) of butylbenzene before the start of the reaction.

[0092] As a result of the evaluation, the yield of the above compound obtained from the functional structure after heating was maintained at 60% or more compared to the yield of the above compound obtained from the functional structure before heating.

[0093] The evaluation results of (1) heat resistance (lifespan) and (2) catalytic activity showed that heat resistance improved when the pore diameter was 0.54 nm or less, and further improved when the pore diameter was 0.45 nm or less, while a certain level of catalytic activity was maintained.

[0094] [Table 1]

[0095] [Table 2] [Explanation of symbols]

[0096] 1 Functional structure 10 Skeleton 10a outer surface 11 Passage 11a hole 12 Expanded diameter part 20 Functional substances 30 Functional substances D C Average particle size D F Average inner diameter D E Inner diameter

Claims

1. A porous support composed of a zeolite-type compound; at least one catalytic material internal to said support; Equipped with The carrier has passages communicating with each other, the passage has one of one-dimensional pores, two-dimensional pores and three-dimensional pores in the framework structure of the zeolite-type compound, and an expanded diameter portion different from any of the one-dimensional pores, the two-dimensional pores and the three-dimensional pores, and the catalytic material is present at least in the expanded diameter portion; the enlarged diameter portion communicates with a plurality of holes constituting any one of the one-dimensional hole, the two-dimensional hole, and the three-dimensional hole, the average inner diameter of the passage is calculated from an average value of minor axes and major axes of pores constituting any one of the one-dimensional pores, the two-dimensional pores, and the three-dimensional pores; an average particle size of the catalytic material is greater than an average inner diameter of the passage and is equal to or smaller than an inner diameter of the expanded portion; the average inner diameter of the passages is 0.54 nm or less; the catalytic material is metal oxide fine particles, the catalytic substance is included in the expanded portion by performing a hydrothermal treatment using a structure-directing agent that defines a skeletal structure of the support after a metal component impregnated in the pores of the ordered mesoporous material has grown into crystals to form the catalytic substance in the pores, The metal component is at least one selected from the group consisting of platinum (Pt), palladium (Pd), ruthenium (Ru), nickel (Ni), cobalt (Co), molybdenum (Mo), tungsten (W), iron (Fe), chromium (Cr), cerium (Ce), copper (Cu), magnesium (Mg), and aluminum (Al). A catalyst structure.

2. 2. The catalyst structure of claim 1, wherein said support supports said at least one catalytic material.

3. 3. The catalyst structure according to claim 1, wherein the metal oxide fine particles have an average particle size of 1.0 nm to 50 nm.

4. 4. The catalyst structure according to claim 1, wherein a ratio of an average particle diameter of said metal oxide fine particles to an average inner diameter of said passages is 1.1 to 500.

5. The catalyst structure according to any one of claims 1 to 4, wherein the inner diameter of the expanded diameter portion is 1.1 nm to 50 nm.

6. 6. The catalyst structure of any one of claims 1 to 5, further comprising at least one other catalytic material carried on the outer surface of the support.

7. 7. The catalyst structure of claim 6, wherein the content of said at least one catalytic material internal to said support is greater than the content of said at least one other catalytic material carried on the outer surface of said support.

8. 8. The catalyst structure according to claim 1, wherein the zeolite type compound is a silicate compound.

9. 9. The catalyst structure according to claim 1, wherein the zeolite type compound comprises one or more framework structures selected from the group consisting of LTA, AFX, LEV, FER and CHA.

Citation Information

Patent Citations

  • Improvement of heat resistance of inorganic mesoporous material

    JP2000072431A

  • Exhaust gas cleaning catalyst

    JP2004148166A

  • Methods for producing and forming supported activated metal catalysts and precursors

    JP2014534902A

  • Method for producing zeolite and zeolite-type

    JP2016529190A

  • Zeolite including metal particle

    JP2017128480A